Analisis Sektor Unggulan Dan Pergeseran Pangsa Sektor-Sektor Ekonomi Kabupaten Klungkung - Aprilia Kesuma, Ni Luh; Suyana Utama, I Made (Jurnal Ekonomi Kuantitatif Terapan, 2015)
Economic growth is an indicator of country’s economic development so that the country should notice its economic growth rate. Klungkung Regency’s economic growth rate is below Bali Province’s economic growth rate during 2008 to 2012. Determination and shift share of the leading sectors in Klungkung can be seen from the contribution of each economic sector to the GDP. There are two purpose of this study is to determine the economic leading sector and shift share of economic sectors in Klungkung. It can be seen from the GDP contribution of each sector during 2008 to 2012. This study using secondary data from BPS Klungkung and BPS Bali. There are two analysis used in this study, those are Location Quotient (LQ) analysis and Shift Share analysis. The result of Location Quotient (LQ) analysis is there are four leading sector of Klungkung which are agriculture sector, mining and quarrying sector, construction sector, and service sector. According to the Shift Share analysis, total (Gij) of service sector has the biggest positive value followed by the industry sector. While agriculture sector has negative value. So it can be said that Klungkung shifting economic structure from agriculture sector to service sector.
Keywords: leading sector; LQ; shift share; Klungkung